THE ROLE OF ENGLISH COMMUNICATION COMPETENCE TOWARD STAR HOTEL STAFFS’ WORKING ACHIEVEMENT IN PALEMBANG - Ega Leovani; Anastasia Ronauli Hasibuan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2018)
Considering the arrangement of upcoming ASEAN Economic Community and Asian games 2018, the potential hotels are urged to prepare qualified and competitive human resource. Language is believed as a means of communication among people involved in these international events. People around the world would stay at certain hotel and English communication competence might relate the conversation between hotel guests and the employees as service provider agent. This study aims to excavate the role of English communication competence toward employees’ working achievement. About three hundreds and fifty three employees from forty four different star hotels in Palembang were involved as the sample. The data is collected by administering two kinds of instrument, namely speaking test (to obtain the condition of their communication competence), questionnaire concerning superior judgement on employees’ working achievement. The results were obtained through the descriptive, percentage, and statistical analysis which is aimed to find out the significant influence of English communication competence toward employee achievement. The findings showed that there was positive influence of English communication competence toward employee achievement.